Quinuera - Soto, Ariel; Paredes Gómez, Eduardo (DOCTV Latinoamérica, 2014)
Irineo has lived in Cochabamba since he was 10 years old. To that place he moved with his parents from Alota, a small town in the highlands dedicated to the cultivation of quinoa. The international quinoa boom makes Irineo, 20 years later, return to his hometown with his wife and his children to seek the improvement that the city has not provided. In Alota, Don Lucio, Irineo's grandfather and community leader, awaits them, who never left his land but who has been a spectator of the progressive abandonment of his inhabitants to different metropolises. Today, Alota faces a future of economic prosperity that threatens to destabilize the daily life of the community, since the elements of the mass commercialization of a product have come into play that, until yesterday, was only a basic food and a close link with Pachamama. --